2017
DOI: 10.1111/1471-0528.14751
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cerebral perfusion with contrast‐enhanced ultrasound during constriction of the neck mimicking malposition of the BD Odon Device™: a study in newborn piglets

Abstract: Objective The BD Odon Device TM is a new instrument for operative vaginal birth with potential for preventing maternal, fetal and newborn morbidity/mortality during a complicated second stage of labour. The device is a plastic sleeve with an air chamber inflated around the baby's head which is gently pulled through the birth canal. The aim was to monitor changes in cerebral circulation during constriction of the neck to evaluate a risk of potential malposition of the device.Design Randomised prospective study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The lack of negative pressure on the fetal head, the mechanism of action of the ventouse, is designed to eliminate vacuum-associated haematoma and haemorrhage. These contentions have been supported in pre-clinical simulation studies [8][9][10].…”
Section: Introductionmentioning
confidence: 83%
“…The lack of negative pressure on the fetal head, the mechanism of action of the ventouse, is designed to eliminate vacuum-associated haematoma and haemorrhage. These contentions have been supported in pre-clinical simulation studies [8][9][10].…”
Section: Introductionmentioning
confidence: 83%
“…The BD Odon Device is the first new device for AVB since the introduction of ventouse into clinical practice in the 1950s [16]. Extensive pre-clinical simulation testing has suggested that it is not likely to generate additional pressure over the fetal head compared with current instruments [9, 17], is not likely to generate clinically significant levels of neonatal hypoxia if misplaced over the fetal carotid arteries [10], and is not likely to be associated with unsafe patterns of use by the target user population [12]. We believe that it is therefore reasonable to proceed to a clinical feasibility study of the device, and, if positive, a randomised controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of negative pressure on the fetal head, the mechanism of action of the ventouse, obviates the risk of haematoma and haemorrhage associated with ventouse. Both of these contentions have been supported in pre-clinical simulation studies [9, 10]. A first-in-human pilot study of an earlier version of the device in healthy volunteers has been completed and demonstrated that assisting birth using the device is feasible [11].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Becton Dickinson and Company (BD) licensed the development rights of the Odon device. In consequence, the trial was paused in January 2015 for BD to conduct preclinical studies [ 13 – 15 ] and develop a new prototype. 3) The third phase included multiparous and nulliparous women with follow-up until discharge at a public tertiary hospital in Pretoria, South Africa (2017).…”
Section: Methodsmentioning
confidence: 99%